Physical Education and Sports Learning in Elementary Schools: Peer Teaching Model Increases Students' Self-Confidence and Responsibility - Sonjaya, Azhar Ramadhana; Ma'mun, Amung; Kusmaedi, Nurlan; Juliantine, Tite (Universitas Pendidikan Indonesia, 2025)
The loss of self-confidence and responsibility in students can be caused by various factors, both internal and external, such as negative experiences, lack of positive support from people around them, and social comparisons between friends. One way that can be used to implement effective learning strategies is to ensure that teachers involve students actively, creatively, and enjoyably so that they feel more motivated to learn. One of the obstacles faced by teachers when implementing physical education is that students do not feel responsible for what they learn towards the learning objectives that are achieved and the use of appropriate learning models. Therefore, to support students' self-confidence and responsibility, the peer teaching learning model can be used in physical education and sports in schools. The purpose of this study was to determine the level of student development towards self-confidence and responsibility by using the peer teaching model. This study uses a pre-experimental method with a one-group pretest–posttest design with the technique purposive sampling in Class VI SDN 1 Cisurupan Garut. Data were obtained using a questionnaire instrument of student self-confidence and responsibility. Research in this area can provide insight into how schools, teachers, and families can build good character in students, as well as identify factors that influence both characters. Self-confidence and responsibility are two main characters that shape a student's behavior, achievement, and social skills.